Pattern of Residential Water Demand Analysis for Maiduguri Metropolis, North-Eastern Nigeria - Abdullah, A.; Ibn Abubakar, B. S. U.; Jones, A. N. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This study investigated the projected 50-year water demand of Maiduguri township from 2006 to 2056. The impact of socio-economic factors on water consumption pattern of the population was also assessed. Data were collected from 200 households using structured questionnaires and analyzed using Statistical Package for the Social Science (SPSS). The results show that on an average, a household in Jere and Maiduguri consumes an estimated 421.85l L/day while areas worst hit are new layouts and those covered by the phase 2 water treatment plant (yet to be completed). In addition, it was found that, gender, education, household size and income were statistically significant predictors of water demand. Furthermore, the results revealed that in 2006, the combined population of Jere and Maiduguri was 749,123, which was later projected to be around 3,618,579 by the year 2056. Similarly, water demand was estimated to rise to approximately 154,443 M3/day by the year 2056 to meet the water demand of the growing population. However, in 2006, the combined water supplied from Maiduguri water treatment plant and all the functional boreholes (public boreholes) stands at 31,973M3/day while in 2016 it rose to 43,811 M3/day. The increase was due to additional supplies obtained from boreholes provided by some Non-Governmental Organization (NGOs) in some locations across the two areas. It is noteworthy that water supplied in the year 2016 to the population was grossly inadequate to meet the household water demand. Therefore, with the projected water demand of about 154,443 M3/day by 2056, it is recommended that all existing water supply schemes including the proposed phase 2 of the Maiduguri surface water treatment plant designed to cover West end, Wulari, Bulunkutu and Maduganari areas to be completed to increase the supply. Service boreholes in newly established layouts should be put to operate at full capacity including the additional ones drilled. Also, the Dala Alamdari mini water works constructed by International Committee of the Red Cross (ICRC) which is operated below its installed capacity due to poor management to be enhanced.